Transcriptomic screen for DIS3, DIS3L1 and DIS3L2-associated functional networks in colorectal cancer - Costa, Paulo (2025)
The final step of cytoplasmic mRNA degradation proceeds in either a 5’-3’ direction, catalyzed by XRN1, or in a 3’-5’ direction catalyzed by the exosome. In yeast, DIS3/Rrp44 protein is the catalytic subunit of the exosome. In humans, there are three known paralogues of this enzyme: DIS3, DIS3L1, and DIS3L2. Important findings over the last years have shed a new light onto the.mechanistic details of RNA degradation by these exoribonucleases. In addition, it has been shown that they are involved in growth, mitotic control and important human diseases, including cancer. For example, DIS3L2 inactivation was associated with mitotic abnormalities and altered expression of mitotic checkpoint proteins (Astuti et al., 2012). In another study, DIS3 was found to be highly expressed in colorectal cancer (CRC), suggesting an oncogenic function (Camps et al., 2013). A major challenge in systems biology is to reveal the cellular networks that give rise to specific phenotypes (Lan et al., 2013). In this project, we aim to analyze how DIS3 and DIS3L1 regulate the human transcriptome, and how their functional interactions modulate the transcriptional reprogramming of colorectal cancer cells. We will perform an extensive characterization of the DIS3 and DIS3L1 mRNA targets, using DIS3 and DIS3L1 knockdown and microarray analysis, in normal colorectal cells, and in different CRC cell lines, in the presence and absence of stress stimuli, such as hypoxia. Differential expression and gene set enrichment analyses of collected data will elucidate new cellular pathways regulated by DIS3 and DIS3L1 and/or by their targets, as well as how they can be involved in CRC. In addition, this analysis may reveal novel functional networks through which the RNA exosome modulates the eukaryotic transcriptome.